놀이치료 슈퍼비전에서 슈퍼바이지 불안정 애착 전략이 슈퍼비전 만족도에 미치는 영향에서 슈퍼비전 관계의 매개효과 - 민미혜; Min Mi-hye; 진미경; Jin Mi-kyoung (한국놀이치료학회지(놀이치료연구), 2022)
본 연구에서는 놀이치료 슈퍼비전에서 슈퍼바이지 불안정 애착 전략이 슈퍼비전 만족도에 미치는 영향에서 슈퍼비전 관계의 매개효과를 검증하였다. 이를 위해 전국의 전문 아동상담기관, 병원 및 복지관 내 놀이치료실, 대학 부설 놀이치료실 등에서 종사하고 있는 놀이치료자 158명을 대상으로 하였다. 수집된 자료는 SPSS 25.0을 사용하여 상관분석을 실시하였으며, Hayes(2013)의 Process Macro를 활용하여 매개효과를 분석하였다. 연구결과를 요약하면 다음과 같다. 첫째, 슈퍼바이지 불안정 애착 전략은 슈퍼비전 관계, 슈퍼비전 만족도와 부적 상관관계가 유의한 것으로 확인되었다. 한편, 슈퍼비전 관계는 슈퍼비전 만족도와 정적 상관관계가 유의한 것으로 확인되었다. 둘째, 슈퍼바이지의 불안정 애착 전략이 슈퍼비전 만족도에 미치는 영향에서 슈퍼비전 관계의 하위요인인 안전기반, 성찰적 교육, 구조화의 매개효과가 유의한 것으로 확인되었다. 이처럼 본 연구에서는 슈퍼바이지 불안정 애착 전략이 슈퍼비전 만족도에 미치는 영향에서 슈퍼비전 관계의 매개효과를 검증하여 슈퍼바이지 불안정 애착 전략과 슈퍼비전 관계, 슈퍼비전 만족도의 관계를 보다 심층적으로 이해할 수 있게 되었다는 점에서 의의가 있다. 또한, 슈퍼비전 만족도를 높이기 위해서는 슈퍼비전 관계가 중요함을 증명함으로써 슈퍼바이저는 슈퍼바이지의 애착 전략에 따라 다르게 개입할 필요성이 시사된다. The purpose of this study is to verify the mediating effects of the supervisory relationship between supervisee insecure attachment strategies and supervision satisfaction as they apply to in play therapy supervision. The major results of this study were as follows. First, attachment strategies had clear, negative correlations with the supervisory relationship and supervision satisfaction. Conversely, the supervisory relationship had a significantly positive correlation with supervision satisfaction. Second, sub-factors of the supervisory relationship (safe base, reflective education, structure) had significant mediating effects between supervisee insecure attachment strategies and supervision satisfaction. In conclusion, this study facilitates an improved understanding of the relationship between supervisee insecure attachment strategies, the supervisory relationship, and supervision satisfaction by verifying the mediating effect of the supervisory relationship between supervisee insecure attachment strategies and supervision satisfaction.